Strategi Penyelesaian Pendaftaran Tanah Hak Komunal Masyarakat Hukum Adat Pandumaan-Sipituhuta - Ardi Saputra Sinaga; Julius Sembiring; Sukayadi Sukayadi (Sekolah Tinggi Pertanahan Nasional, 2019)
Abstract: Environment and Forestry Ministry established the reserve incense forest of the Pan-dumaan-Sipituhuta Customary Law Community as a customary forest. But in reality, it has not been guaranteed legal certainty regarding the existence and recognition of the rights of the Pan-dumaan-Sipituhuta Customary Law Community. The objective of this research is to know the le-gal status of Indigenous Peoples forest in Pandumaan-Sipituhuta Customary Law at this time, strategy of the land registration of communal right settlement, and constraint and effort done in the land registration of communal right settlement of Pandumaan-Sipituhuta Customary Law Community. This research uses qualitative research method with empirical juridical research form. Based on the results of the study showed that the legal status of the Indigenous Forests of Pandumaan-Sipituhuta Customary Law Society is currently reserved as customary forest of Pan-dumaan-Sipituhuta Customary Law Community. Strategy for resolving communal rights land registration in the incense forest of the Pandumaan-Sipituhuta Customary Law Community through four stages. First, recognition of the existence of the Pandumaan-Sipituhuta Customary Law Community. Secondly, the establishment of customary forests of the Pandumaan-Sipituhuta Customary Law Community by Environment and Forestry Ministry. Third, the Settlement of Land Control in Forest Areas is carried out in accordance with Presidential Regulation Number 88 of 2017 by issuing customary forests of the Pandumaan-Sipituhuta Customary Law Community from forest areas. Fourth, registration of communal land rights of Pandumaan-Sipituhuta Custom-ary Law Community.Keywords: strategy, communal rights, customary forestsIntisari: Kementerian Lingkungan Hidup dan Kehutanan (KLHK) menetapkan pencadangan hutan kemenyan Masyarakat Hukum Adat Pandumaan-Sipituhuta sebagai hutan adat. Tetapi kenyataannya, keadaan tersebut hingga saat ini dinilai belum menjamin kepastian hukum akan keberadaan dan pengakuan hak Masyarakat Hukum Adat Pandumaan-Sipituhuta. Tujuan dari penelitian ini untuk menjelaskan bagaimana strategi penyelesaian pendaftaran tanah hak komunal hutan kemenyan Masyarakat Hukum Adat Pandumaan-Sipituhuta. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan yuridis empiris. Berdasarkan hasil penelitian menunjukan bahwa status hukum hutan kemenyan Masyarakat Hukum Adat Pandumaan-Sipituhuta saat ini dicadangkan sebagai hutan adat. Strategi penyelesaian pendaftaran tanah hak komunal hutan kemenyan Masyarakat Hukum Adat Pandumaan-Sipituhuta melalui empat tahapan. Pertama, pengakuan keberadaan Masyarakat Hukum Adat Pandumaan-Sipituhuta. Kedua, penetapan hutan adat Masyarakat Hukum Adat Pandumaan-Sipituhuta oleh KLHK. Ketiga, dilakukan Penyelesaian Penguasaan Tanah dalam Kawasan Hutan sesuai dengan Peraturan Presiden Nomor 88 Tahun 2017dengan cara mengeluarkan hutan adat Masyarakat Hukum Adat Pandumaan-Sipituhuta dari kawasan hutan. Keempat, pendaftaran tanah hak komunal Masyarakat Hukum Adat Pandumaan-Sipituhuta.Kata Kunci : strategi, hak komunal, hutan adat